ART THERAPY: EXPLORING THE RELATIONSHIP BETWEEN ART THERAPY AND SPIRITUAL HEALING - Khurana, Rakshita; Wadhawan, Vidisha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Art therapy has been used to aid spiritual healing because it allows people to express and explore their deepest thoughts, emotions, and experiences in a safe and supportive environment. Spiritual healing is a holistic approach that includes reestablishing one’s sense of connection to something greater than oneself, likely to result in emotional, physical, and spiritual well-being. The objective of this study is to investigate the role of art therapy in facilitating spiritual healing in individuals. A comprehensive review of literature was conducted to identify the current state of knowledge on the topic. The review identified studies that explored the effectiveness of various types of art therapy in supporting spiritual healing. According to the conclusions drawn from the literature review, art therapy can be an effective instrument in aiding spiritual healing through practices like meditation and mindfulness. Art therapy provides a safe and non-judgmental space for individuals to explore their spirituality, leading to a sense of connection to something greater than themselves. Further to that, the creative process of art-making can promote emotional release and catharsis, resulting in a sense of inner peace and healing. Overall, the results indicate that art therapy can be an efficient means of helping people heal spiritually. The integration of spiritual practices into the art therapy process can support individuals in their journey towards emotional, physical, and spiritual well-being, leading to a greater sense of inner peace and connection to the world around them.